Knowledge, Attitude and Practice of Menstrual Hygiene among Primary School Adolescents in Surabaya, Indonesia - Pinesa Rachma Andani (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Menstruation is a normal physiological process of an adolescent female. Adolescence is a very important transition period that requires special attention to ensure progress for all girls. Some studies found that menstruation is taboo to be discussed and many girls just known about menstruation when they have menarche. The genitourinary becomes more sensitive and susceptible to infection during the menstruation period. So the appropriate menstrual hygiene practice is very important to maintain the health of reproductive organs. This study objective is to asses the current knowledge, attitude, and practice of primary school adolescents on menstrual hygiene management in Surabaya, Indonesia. Method: This is a descriptive cross-sectional study that was carried out from May to June 2019 in a primary school in Surabaya. This study was done among 78 students selected through total population sampling from a primary school in the urban area of Surabaya. Results: The findings showed that 66,7% of participants have good knowledge, 60,3% have a good attitude and 79,5% have good practice regarding menstrual hygiene. Conclusions: The majority of the participants have good knowledge, attitude and practice regarding menstrual hygiene. Nevertheless, the knowledge, attitude, and practice of all the participants still need to improve. The school along with the parents and health provider are expected to reinforce the health education program about menstrual hygiene management.